Малопургинская земля - моя родина - Зорина Валентина Спиридоновна (Удмуртия, 2002)
Экземпляры: аб. ДБ (2016.19.12) / Инвентарный номер: 2914 / Цена: / Сис.шифр: 63.3(2Рос.Удм) / Авт.знак: М 19 / ГРНТИ: 03 / ББК: 63.3(2Рос.Удм)